FRI0536 SERUM GOLIMUMAB CONCENTRATIONS AND ANTI-DRUG ANTIBODIES ARE ASSOCIATED WITH TREATMENT RESPONSE AND DRUG SURVIVAL IN PATIENTS WITH INFLAMMATORY JOINT DISEASES: DATA FROM THE NOR-DMARD STUDY. (2nd June 2020) - Gehin, J. E.; Warren, D. J.; Syversen, S. W.; Lie, E.; Sexton, J.; Loli, L.; Wierød, A.; Bjøro, T.; Kvien, T. K.; Bolstad, N.; Goll, G. L.
Abstract : Background: Lack or loss of response to TNFα-inhibitors can be caused by subtherapeutic drug levels and anti-drug antibodies (ADAb). Knowledge about associations between clinical efficacy and drug levels as well as occurrence of ADAb is limited in patients with inflammatory joint diseases (IJD) treated with golimumab. Objectives: To identify the therapeutic target concentration and assess the frequency of ADAb in golimumab-treated patients with IJD. Methods: 91 patients from the NOR-DMARD study with a clinical diagnosis of axial spondyloarthritis (n=41), rheumatoid arthritis (n=20) or psoriatic arthritis (n=30) starting treatment with golimumab, with an available biobank sample at 3 months follow-up, were included. Treatment response was defined by ASDAS Clinically important improvement in axial spondyloarthritis, EWULAR good/moderate response in rheumatoid arthritis and improvement of ≥50% in modified DAPSA (using 28 swollen/tender joint counts) in psoriatic arthritis. Serum drug concentrations were analysed in non-trough samples collected 3 months after treatment initiation, using an automated in-house target-based immunofluorometric assay. ADAb was measured with an inhibition assay that measures neutralising antibodies. The association between drug levels and treatment response was assessed by multivariable logistic regression (adjusted for age, sex and prior bDMARD (Y/N)). Drug-survival was assessed by Kaplan-Meier curves and Cox proportional hazard regression analysis. Results: Golimumab serum concentrations varied considerably between patients on standard dose (range 0.0-8.2 mg/L) with a median of 2.2 (IQR 1.0-3.5) mg/L. The proportions of responders after 3 months among patients with golimumab concentration <1.0, 1.0-3.9 and ≥4.0 mg/L, were 19%, 49% and 74%, respectively (Fig.1 ). The likelihood of response after 3 months of treatment was significantly higher among patients with serum golimumab concentration ≥1.0 mg/L compared to those with golimumab <1.0 mg/L (OR 5.8 (95% CI 1.7-19.7), P =0.005). The proportion of responders was highest among patients with golimumab concentrations ≥4.0 mg/L, but the difference in response between patients with concentrations ≥4.0 mg/L compared to 1.0-4.0 mg/L was not statistically significant (OR 2.1 (95% CI 0.6-7.1), P=0.24). We also found a higher rate of treatment discontinuation in patients with serum golimumab concentration <1.0 mg/L compared to ≥1.0 mg/L (HR 3.6 (95% CI 1.9-6.9), P <0.001) (Fig.2 ). ADAb were detected in 5 of 91 samples and were associated with lower drug concentrations. Only 1 out of 5 ADAb-positive patients was a responder at 3 months, and all 5 ADAb positive patients discontinued treatment within the first 14 months. Conclusion: Golimumab concentrations ≥1.0 mg/L were associated with improved treatment response and better drug survival, but our results also indicate that some patients might benefit from higher concentrations. ADAb were associated with lower drug concentrations and both reduced treatment response and drug survival. These findings suggest a rationale for personalised dosing guided by measurements of drug concentration and ADAb in golimumab-treated patients with IJD, which should be addressed in future randomised strategy trials. Disclosure of Interests: Johanna Elin Gehin Speakers bureau: Roche, David J Warren: None declared, Silje Watterdal Syversen Speakers bureau: Roche, Thermo Fisher, Elisabeth Lie: None declared, Joe Sexton: None declared, Liz Loli: None declared, Ada Wierød: None declared, Trine Bjøro: None declared, Tore K. Kvien Grant/research support from: Received grants from Abbvie, Hospira/Pfizer, MSD and Roche (not relevant for this abstract)., Consultant of: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Paid instructor for: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Speakers bureau: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Nils Bolstad Consultant of: Pfizer, Janssen, Speakers bureau: Orion Pharma, Napp Pharmaceuticals, Takeda, Roche, Novartis, Guro Løvik Goll Consultant of: Novartis, Pfizer, Speakers bureau: Abbvie, Biogen, Boehringer Ingelheim, Orion Pharma, Eli Lilly, Novartis, Pfizer, MSD, Roche, UCB